Adult Bone Marrow Cell Therapy for Ischemic Heart Disease. Issue 6 (28th August 2015) - Afzal, Muhammad R.; Samanta, Anweshan; Shah, Zubair I.; Jeevanantham, Vinodh; Abdel-Latif, Ahmed; Zuba-Surma, Ewa K.; Dawn, Buddhadeb
<x xml:space="preserve">Abstract</x> Rationale: Notwithstanding the uncertainties about the outcomes of bone marrow cell (BMC) therapy for heart repair, further insights are critically needed to improve this promising approach. Objective: To delineate the true effect of BMC therapy for cardiac repair and gain insights for future trials through systematic review and meta-analysis of data from eligible randomized controlled trials. Methods and Results: Database searches through August 2014 identified 48 eligible randomized controlled trials (enrolling 2602 patients). Weighted mean differences for changes in left ventricular (LV) ejection fraction, infarct size, LV end-systolic volume, and LV end-diastolic volume were analyzed with random-effects meta-analysis. Compared with standard therapy, BMC transplantation improved LV ejection fraction (2.92%; 95% confidence interval, 1.91–3.92; P<0.00001), reduced infarct size (−2.25%; 95% confidence interval, −3.55 to −0.95; P=0.0007) and LV end-systolic volume (−6.37 mL; 95% confidence interval, −8.95 to −3.80; P<0.00001), and tended to reduce LV end-diastolic volume (−2.26 mL; 95% confidence interval, −4.59 to 0.07; P=0.06). Similar effects were noted when data were analyzed after excluding studies with discrepancies in reporting of outcomes. The benefits also persisted when cardiac catheterization was performed in control patients as well. Although imaging modalities partly influenced the outcomes, LV ejection fraction improved in BMC-treated patients when assessed by magnetic resonance imaging. Early (<48 hours) BMC injection after myocardial Infarction was more effective in reducing infarct size, whereas BMC injection between 3 and 10 days proved superior toward improving systolic function. A minimum of 50 million BMCs seemed to be necessary, with limited additional benefits seen with increasing cell numbers. BMC therapy was safe and improved clinical outcomes, including all-cause mortality, recurrent myocardial Infarction, ventricular arrhythmia, and cerebrovascular accident during follow-up, albeit with differences between acute myocardial Infarction and chronic ischemic heart disease subgroups. Conclusions: Transplantation of adult BMCs improves LV ejection fraction, reduces infarct size, and ameliorates remodeling in patients with ischemic heart disease. These effects are upheld in the analyses of studies using magnetic resonance imaging and also after excluding studies with discrepant reporting of outcomes. BMC transplantation may also reduce the incidence of death, recurrent myocardial Infarction, ventricular arrhythmia, and cerebrovascular accident during follow-up.